Analysing The Factors Influencing DevOps Adoption in The Existing DevOps Adoption Models: A Systematic Review (Open International Journal of Informatics, 2022)
DevOps is a modern software process that evolved to fill the gap between software development (Dev) and IT operation (Ops) teams emphasising collaboration. Breaking the silos amongst the software developers and IT Operations teams is essential to achieve the same goal in the software process and deliver quality software. However, there are relatively few DevOps models in the literature. Practitioners have different perspectives on how to adopt DevOps. Thus, understanding the factors that influence the decision-making toward DevOps adoption is crucial. Even though previous studies have discussed the factors influencing DevOps adoption, this paper will identify the factors stated in the existing DevOps adoption models. We conducted a systematic literature review on the DevOps adoption model and identified six related DevOps adoption models. Next, we identified the factors influencing DevOps adoption highlighted in the models. The factors highlighted are automation, collaboration, sharing, measurement, resilience, agility, develop and deploy  cloud-based application, quality, continuous improvement, and leadership.
Keywords: DevOps; DevOps adoption model; automation; collaboration; sharing; measurement; resilience; agility; cloud-based application; quality; continuous improvement; leadership